Human capital and structural transformation in Sub-Saharan Africa - (:unkn) unknown (My University, 2023)
This thesis explores not only the different effects of human capital on industrialization and export diversification in Sub-Saharan African economies (SSA), but also the channels through which these effects are channelled to boost structural transformation of these economies. It also distinguishes the nature of these effects according to the institutional context. Using a dynamic panel model based on the method of generalised moments in a system applied to a sample of thirty African economies over the period 1995-2018, estimates were made using data from the World Bank (Word Development Indicators), UNCTAD (UNCTADSTAT), the Groningen Centre for Economic Growth and Development, in particular the Penn World Table (recent version, 10.0) and the International Country Risk Guide (ICRG) of the Political Risk Services group. These estimates lead to four main groups of results. The first group shows that the effect of human capital on industrialization is mediated by the type of education and is captured by the positive and significant relationship between enrolment rates in secondary and tertiary education and manufacturing value added; the enrolment rate in primary education generates varying effects. The second group of results highlights the positive and significant relationship between human capital formation, as measured by the higher education enrolment rate, and the quality of institutions, as measured by a composite index. The third group of results highlights a threshold effect attributable to human capital formation, the effect of which on diversification becomes positive and significant above a certain level of investment. The fourth group of results is structured by the technological absorption capacity made possible by investment in human capital. These results have serious theoretical implications for the recognised relationship between investment in human capital and growth via the structural transformation of economies. This places investment
Keywords: African Research